Temas e figuras do mito de Orfeu nas Geórgicas de Virgílio: (Virgílio, Geórgicas, IV, 453-527) - Bertini, Beatriz Scatena [UNESP] (2017)
This research presents the Latin text using the theoretical instrument provided by Linguistics, Poetics and Literary Semiotics, focusing mainly on the aspects of the figurative discourse. Therefore, the perception of the effects of meaning, learned through the reading of the text, was needed in order to discover the resources of selection and combination responsible for these effects. The corpus is an excerpt from Virgil's Georgics (verses number 453 to 527), and, as a result of investigation of this episode that narrates the Myth of Orpheus, a metalinguistic discourse has been produced. This analysis and description of the text concentrated mainly on the first stage of the proceedings of figurativization, when one observes the manifestation of a theme from semiotic figures